Nutrient retention by different substrates from an improved low impact development system. (15th May 2019) - Zhou, Junjie; Liang, Xinqiang; Shan, Shengdao; Yan, Dawei; Chen, Yanfeng; Yang, Chunke; Lu, Yuanyuan; Niyungeko, Christophe; Tian, Guangming
Abstract: The reuse of water in agriculture has become more common in water management worldwide. However, there is very limited information about nutrient retention in water reclamation management. In this study, an improved low impact development (LID) practice was constructed to investigate the synergistic effects of three substrates amendment on nitrogen (N) and phosphorus (P) retention under two irrigation modules: spray and drip irrigation. The orthogonal combination of the three substrates was controlled during four leaching events, with polyacrylamide (PAM), peat soil, and straw biochar application rates of 1, 2, and 4 g kg −1 ; 5, 10, and 20 g kg −1 ; and 10, 20, and 40 g kg −1, respectively. Results showed that the optimum treatments for N and P were 2 g kg −1 of PAM; 2 g kg −1 of PAM, 10 g kg −1 of peat soil, and 40 g kg −1 of straw biochar, respectively. The highest amounts of N and P retention under spray and drip irrigation were 83.12 mg N kg −1 and 50.09 mg N·kg −1, and 11.88 mg P·kg −1 and 7.47 mg P·kg −1, respectively. The analysis of variance indicated that PAM, biochar, and peat soil affected the retention of leachate, N, and P differently. PAM application could not only improve the water, N, P retention capacity of soil, but also significantly increase the content of ＞2 mm water-stable soil aggregate (WSA) ( p ＜0.05), and there is an advisable linear relation between N, P retention and the content of ＞2 mm WSA ( R 2 = 0.79, 0.67, respectively). Overall, this study concludes that a combined application of PAM and biochar could reduce P loss and increase the ＞2 mm WSA under leaching condition. Highlights: An improved low impact development system packed with different substrates can retain leachate nitrogen and phosphorus. PAM application rate at 2 g·kg −1 of soil achieved the maximum amount of nitrogen and phosphorus retention from LID systems. PAM combined with biochar can reduce phosphorus loss and enhance the water retention capacity of soil from LID systems.